Effects of In Ovo Vitamin D3 Injection on Subsequent Growth of Broilers - Takehiko Hayakawa; Jun-ichi Shiraishi; Yoshiyuki Ohta (The Journal of Poultry Science, 2019)
This study was conducted to investigate the influence of in ovo vitamin D3 (Vit D3) administration on growth of broiler chickens when Vit D3 was dissolved in soybean oil. Sixty Ross broiler eggs were incubated at 37.8°C and >60% relative humidity. Distilled water, soybean oil, or Vit D3 (60 IU / 0.5 mL) dissolved in soybean oil, was administered in ovo on Day 18 of incubation. Seven days after hatching, chicks were sexed, and 12 birds (six female and six male) close to the average body weight (BW) of each treatment were selected and their BW continuously recorded until 28 days of age, then sacrificed. Liver and pectoral muscle were collected to determine the mRNA expression of IGF-1 and IGF-1 receptor, and the length of tibia was measured. There were no significant differences in BW, liver weight, or pectoral muscle weight between the groups. However, an interaction was observed between treatments and sexes in the tibia length. In comparison among only males, tibia length in the Vit D3 with oil group was longer than that of the control, but not different from that of the oil group. The same tendency was observed in the hepatic IGF-1 mRNA expression in chicks of either sex, with this effect only being observed after the treatments and not in the control. On the other hand, there was an interaction between treatments and sexes in the mRNA expression of IGF-1 receptor, which was highest in the Vit D3 with oil group in females, but not in males. These results indicated that the in ovo administration of Vit D3 affected IGF-1 receptor mRNA expression without growth.